2021
DOI: 10.18052/www.scipress.com/jhpr.13.10
|View full text |Cite
|
Sign up to set email alerts
|

Effect of NPK Fertilizer Rates on Growth and Yield of Field and Greenhouse Grown Pepino Melon (<i>Solanum muricatum</i> Aiton)

Abstract: Pepino melon (Solanum muricatum Ait.) is an exotic vegetable whose consumption is on the increase in Kenya due to its health and nutritional benefits. A study was conducted at Egerton University, Kenya in 2018-2019 to investigate the effect of NPK fertilizer rates (0, 100, 200. 300 and 400 kg ha-1) on growth and yield of field and greenhouse grown pepino melons. The experiment was laid in a randomized complete block design with three replications. Data was recorded on plant height, stem diameter, number of lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Some studies have shown that the treatment of plants with solutions and mixtures of mineral salts such as NPK increased the accumulation of polyphenolic compounds several times over in comparison with test plants [16,17]. On the other hand, there is evidence of a significant decrease in the amount of soluble phenolic compounds and flavonoids in different plants under the influence of NPK [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that the treatment of plants with solutions and mixtures of mineral salts such as NPK increased the accumulation of polyphenolic compounds several times over in comparison with test plants [16,17]. On the other hand, there is evidence of a significant decrease in the amount of soluble phenolic compounds and flavonoids in different plants under the influence of NPK [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Mostly, vegetable plants from the Cucurbitaceae family shortly after flower formation fail to fertilize the embryo and cause the bisexual flower or pistil to abort due to genetic makeup or environmental conditions, resulting in decreased yield/plant [64,65]. The combined application of NAA and potassium nitrate will significantly increase the vitality and activity of the female flower and this will, therefore, reduce abortion and improve the chances of fertilization occurring [60,66,67]. Potassium helps plants remain physiologically active, building enough food to develop flowers and fruits, which in turn ultimately leads to increased productivity [2,60,68].…”
Section: Effect Of Potassium Nitrate and Naa On The Flowering Stagementioning
confidence: 99%
“…NPK manure at optimal doses increases secondary metabolites in plants. However, adding NPK manure above its optimum dosage will decrease the accumulation of secondary metabolites because the plant will allocate most of the nutrition for its growth and development [5].…”
Section: Cuprac Assaymentioning
confidence: 99%
“…A lack of nitrogen promotes the accumulation of non-nitrogenous metabolites, such as phenols and terpenoids. In contrast, enough nitrogen fertilizer encourages nitrogenous secondary metabolite accumulation, such as cyanogenic glycosides and alkaloids [5]. Soil factors such as macroelements (N, P, K) and microelements (Fe, Zn, and Mn) influence bioactive substance synthesis in plants.…”
Section: Introductionmentioning
confidence: 99%